Geração I: habitus virtuais e sociabilidades em escolas públicas e privadas de Fortaleza - Lopes, Paula Cristina Barros (2021)
With the popular and instantaneous advent of Social Networks, Generation I from Internet (also known as Z and post-millennial) – which comprises people born after the 1990s, the generation that was born and grew up with advertising of the Internet – started to consume knowledge and information, as well as to communicate and relate using digital technology. Moreover, young people who were born especially after the 2000s, concomitant to the popularization of the Internet and mobile digital technology, grew up on the network and in the network, or better said in cyberspace, having the provision in real time: information, communication, training and leisure mediated by the so-called smart phones “Smartphones”, which, therefore, led us to consider that they built new ways of relating in the digital environment, they created both virtual habitus and sociability, which were incorporated, daily, within the virtual environment. Thus, it was intended to research how we could understand the influence of this phenomenon, which was born from the union of the social with digital technology, in the virtual habitus and in the sociability of these young people who were experiencing their personal and relational experiences, within cyberspace; or yet investigate if there were similarities and differences in these virtual habitus and in these experienced sociability, within social networks, between young people from different schools and social classes, from a comparative study that was carried out between two formats of Public School (State’s School of Professionalizing Education and Elementary and Secondary Schools) and a Private School format (Private School of Upper Middle Class). So, the methodology included a mixed analysis model, with qualitative techniques (questionnaire and focus group), and quantitative tools (sample calculation and software that allows comparative analysis). Therefore, the results of the research showed that, Generation I’s young people, regardless of the school format, incorporated both the virtual habitus and the sociability experienced within the Internet and social networks into their daily lives, especially in the last decade.